Going Solo or in Numbers? Perspective of Secondary Teachers on Classroom Rules Establishment - Letuma, Motsekiso (COMPETITIVE: Journal of Education, 2024)
Effectively managing a classroom requires teachers to establish clear rules for acceptable and inappropriate behaviour in the learning environment. These rules assist teachers in managing diversity since learners come from various backgrounds. Evidence indicates the existence of classroom indiscipline in secondary schools in South Africa. This study explored how secondary schools established classroom rules. The study was grounded on general systems theory, utilised the interpretivism paradigm, employed a qualitative approach and a multiple case study design. Three data collection instruments were used: document analysis, semi-structured interviews, and focus group interviews. Inductive content analysis was used to analyse the generated data. The findings revealed that some sampled schools have not established classroom rules. For the schools that do, establishing the rules rests on teachers’ individual practices and expertise since the rules range from six to eighteen in different classes and are in written in positive and negative language. The study concludes that professional development opportunities for teachers regarding effective classroom rule establishment are minimal in schools. This study suggests that the department capacitated teachers to establish classroom rules and monitor adherence. The study offers a transformative change, shifting the focus of professional development from solely curriculum implementation to also encompassing classroom behaviour management strategies in schools.